2021
DOI: 10.21037/atm-20-5001
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Review of Carotid disease and the kidney

Abstract: Patients with chronic kidney disease (CKD) have an increased cardiovascular (CV) risk that is only in part explained by established risk factors. Carotid arteriosclerosis and atherosclerosis are increased in CKD, play a role in the causation of CV disease in these patients and can affect the progression of renal disease. The arterial stiffening process is evident even in CKD patients with a very mild reduction of glomerular filtration rate (GFR) whereas arterial thickening is evident in more advanced stages. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 132 publications
(141 reference statements)
0
6
0
Order By: Relevance
“…In the univariate analysis, age > 50 years, female sex, SUR > 6.9 mg/dL, ACR > 30 mg/g, DM, HbA1c % > 7.5, LV mass > 140 g, presence of carotid plaques, obesity, AF, and HF were associated with the risk of developing CKD. There are contradictory details on these relationships, but growing evidence suggests that there are correlations that could be bidirectional between these biomarkers and the cardiovascular clinical and subclinical manifestations and renal damage [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. From the multivariate analysis, after adjusting for age, sex, and DM status, only SUR > 6.9 mg/dL (OR: 6.61; 95% CI: 2.063, 10.83; p = 0.004) and the presence of carotid plaques as a marker surrogate of atherosclerosis (OR: 2.09; 95% CI: 1.1, 2.31; p = 0.07) were independent risk factors of CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the univariate analysis, age > 50 years, female sex, SUR > 6.9 mg/dL, ACR > 30 mg/g, DM, HbA1c % > 7.5, LV mass > 140 g, presence of carotid plaques, obesity, AF, and HF were associated with the risk of developing CKD. There are contradictory details on these relationships, but growing evidence suggests that there are correlations that could be bidirectional between these biomarkers and the cardiovascular clinical and subclinical manifestations and renal damage [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. From the multivariate analysis, after adjusting for age, sex, and DM status, only SUR > 6.9 mg/dL (OR: 6.61; 95% CI: 2.063, 10.83; p = 0.004) and the presence of carotid plaques as a marker surrogate of atherosclerosis (OR: 2.09; 95% CI: 1.1, 2.31; p = 0.07) were independent risk factors of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…If the clinical arguments are strong enough to recommend a ULD in symptomatic subjects (the goal would be to lower SUR < 6 mg/dL), for those who are asymptomatic, there is an unmet need to develop a carefully designed RCT to determine the role of uric acid in the progression of CKD [ 67 ]. The presence of carotid atherosclerotic plaques is well recognized as a marker of atherosclerosis, which in patients with CKD, plays a role in the development of CV disease and could enhance the progression of renal disease [ 51 ]. Even if the results in our study have only borderline statistical significance due to the limited sample size, we found more carotid plaques among subjects with CKD (refer to Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis and carotid arteriosclerosis are more prevalent in CKD. Even in CKD patients with a relatively slight decline in glomerular filtration rate (GFR), the arterial stiffening is prominent, but arterial thickness is only noticeable in more advanced stages [ 28 ]. In another study, it was shown that a family history of stroke and coronary heart disease (CHD) were significantly associated with the presence of CS, independent of conventional risk factors.…”
Section: Reviewmentioning
confidence: 99%
“…The prevalence of CKD is increasing globally, ranging between 8% and 16%, and it is associated with atheromatous CVD owing to the deleterious effects of uremic toxins on the structure and function of arteries. [ 3 4 5 ] With a mortality rate that is 10–30 times greater than the general population, CVD are the major cause of death in patients with ESRD and CKD with dialysis treatment. [ 6 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] Changes in the vascular system in uremic patients are attributed to the synergistic action of numerous factors, such as prothrombotic factors, dyslipidemia, anemia, hypertension, increased oxidative stress, disruption of the synthesis of parathormone (PTH), homocysteine, and nitric oxide, abnormalities of endothelial function, which leads to remodeling of the vascular system. [ 4 5 13 14 ]…”
Section: Introductionmentioning
confidence: 99%